PENILAIAN RISIKO (RISK ASESSMENT) Penerapan Manajemen Resiko pada Kantor Wilayah Direktorat Jendral Perbendaharaan Yogyakarta - , Nanang Trimanta, Dr. Sumiyana, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Public sector organization that serve the community must proactively ensure that the changes can be anticipated, in order to reach organizational goals in accordance with the vision and mission of the organization. The anticipation within the framework of good corporate governance because of the changes that occur can be a beneficial impact but can also adversely affect or risk. This implementation can be effective when considering the risk factors. The goal is to identify activities or business processes that have a significant level of risk by using a scale of priorities, so the monotoring activity can be more focused and can improve cost efficiency. Minister of Finance Regulation 191/PMK.09/2008 explain that the organization in the Ministry of Finance environmental must be require to implement risk management. One of the risk management process is risk assessment. This activity can build an effective early warning system in controlling risk. Risk assessment carried out by measuring the level of risk based on the Impact and Likelihood. After that, the results obtained are included in a risk matrix, which describes the level of risk to the activities conducted at the Kanwil Ditjen Perbendaharaan Yogyakarta. Data collection for the "Impact" is obtained from the identification 82 indicators of risk factors, while for the " Likelihood" is obtained from the questionnaires with respondents consisting of officials at Kanwil Ditjen Perbendaharaan Yogyakarta. Based on the results of risk assessment in this research, the conclusion is quite close to the conditions on the risk level at Kanwil Ditjen Perbendaharaan Yogyakarta. Implementation of risk assessment have weaknesses that need to be repaired. Advice on this research is to make improvements in risk assessment, which adds to the risk assessment based on the type of risk, risk assessment provides an application program and adding other risk indicators that come from outside the organization.